RNA transcripts in salivary extracellular vesicle cargo isolated from aged populations - Wen, Sicheng; Yu, Chang; Kelsey, Maxfield M. G.; Pereira, Mandy; Alaimo, Hannah; Teixeira, Em; Pracht, Jenna; Daiello, Lori A.; Drake, Jonathan; Sedivy, John M.; Wu, Zhijin; Quesenberry, Peter; et al. (Frontiers in Aging, 2026)
IntroductionHuman saliva contains numerous factors, including DNA, RNA, and protein, that may reflect the health status of the individual. Many of these factors are contained within extracellular vesicles (EVs). The contents of EVs are thought to mirror the cytoplasm of the cell of origin, providing insight into the health of the cell. We investigated the RNA content from EVs isolated from saliva (salEVs) to determine if we could detect transcripts associated with neurodegenerative conditions.MethodsWe characterized the RNA cargo of salEVs isolated from individuals over the age of 65 with normal cognition. The salEV RNA content was analyzed by RNA-seq and NanoString miRNA analysis.ResultsWe found approximately 48.4% of the reads mapped to the human genome, with the remainder mapping to prokaryotic genomes. The transcripts included protein-coding RNA, long non-coding RNA, retrotransposons, and miRNAs. A significant number of the protein-coding transcripts were associated with pathways involved in neurodegenerative conditions. In addition, there was an enrichment of transcripts containing AP-2ε, HEYL, HES4, and TCFL5 transcription factor binding sites. We found that the lncRNA content was similar between samples, with PCBP1-AS1, TEX41, and PVT1 being the top represented transcripts. There were 286 miRNAs found in the salEV samples. The pathways predicted to be affected by the top represented miRNAs include Hippo signaling, TGF-β signaling, Wnt signaling, FoxO signaling, ErbB signaling, axon guidance, and mTOR signaling. We could detect retrotransposon transcripts from LINE, SINE, and LTR elements in salEVs. When compared to blood-derived EVs, salEVs showed greater representation of transcripts associated with neurodegenerative pathways.DiscussionOur results indicate that salEVs contain transcripts that are associated with pathways involved in neurodegeneration. The presence of these transcripts in salEVs suggest that saliva may be used to screen for biomarkers of neurodegenerative diseases.